RANCANG BANGUN SISTEM PEMANTAUAN DAN PERINGATAN DINI PARAMETER LINGKUNGAN MIKRO BUDIDAYA TANAMAN PADA RUMAH TANAMAN BERBASIS SMS (SHORT MESSAGE SERVICE) - Mohamad Solahudin; Yudi Chadirin; Gumilang Agus Gozali (Jurnal Keteknikan Pertanian, 2006)
ABSTRACT SMS (Short Message Service) is one of technology can be use alternative to develop greenhouse micro climate monitoring and alert system. This technology selected because of simplicity in information access and widely spread use as comunication tools. The purpose of this research is to develop greenhouse Micro Climate Monitoring and Alert System by combining SMS technology, Portable Weather Station and Mobile FBUS V 1.5. System test performance for variouse provider shows the result wihch vary. The results shows that this system can be applied as monitoring and alert system technology. The performance test shows thaht the average of time service from all communication providers is 24,45 second, with 2.65 lag time. Keyword: Greenhouse, Micro Climate, SMS.n Diterima: 29 September 2006; Disetujui: 16 Nopember 2006